Guidelines for the Successful Regional Integration of Financial Infrastructures - World Bank (Washington, DC, 2015)
Over the past decade or so, the prospects of long term economic, institutional and social gains from regional and global financial and trade liberalization have become more appealing to public and private stakeholders. Indeed, since the late 1980’s both developing and advanced economies have seen greater levels of cross-border banking and the cross-border trading, issuance and investment in securities and financial derivatives. At the same time, recent events like the global financial crisis that emerged in 2008 have prompted market participants, their supervisors and other national authorities, international organizations and standard setting bodies to support more robust and ultimately effective mechanisms to enable cross-border financial market connectivity and liquidity, for the benefit of overall financial stability and also of the final users of cross-border financial services.The guidelines are designed to correspond to themain public and private sector objectives for financial market and infrastructure integration, and to facilitate stakeholder realization of the main benefits that are typically associated with FI integration. The guidelines also address commonly experienced barriers and challenges to efficient, effective and safe regional financial infrastructure integration, in order to improve accessibility and reachability for customers and to help minimize the various costs and risks often associated with integration efforts like these.